Embedded Fin‐Like Metal/CNT Hybrid Structures for Flexible and Transparent Conductors. Issue 11 (14th January 2016) - Jiang, Di; Wang, Nan; Edwards, Michael; Mu, Wei; Nylander, Andreas; Fu, Yifeng; Jeppson, Kjell; Liu, Johan
Abstract : In this paper, an embedded fin‐like metal‐coated carbon nanotube (Fin‐M/CNT) structure is demonstrated for flexible and transparent conductor wire applications. Embedded in a polydimethylsiloxane polymeric substrate, Fin‐M/CNT wires with a minimum width of 5 μm and a minimum pitch of 10 μm have been achieved. Direct current resistances of single Fin‐M/CNT wires, where the supporting CNT structures have been covered by Ti/Al/Au metal coatings of different thicknesses, have been measured. The high aspect ratio of the fin‐like structures not only improves the adhesion between the wires and the polymeric substrate, but also yields a low resistance at a small surface footprint. In addition, transparent Fin‐M/CNT grid lines with hexagonal patterns, with a sheet resistance of as low as 45 Ω sq −1, have been achieved at an optical transmittance of 88%. The robustness of the Fin‐M/CNT structures has been demonstrated in bending tests up to 500 cycles and no significant changes in wire resistances are observed. Abstract : An embedded fin‐like metal‐coated carbon nanotube (Fin‐M/CNT) structure is demonstrated for flexible and transparent conductor wire applications.Embedded in a polydimethylsiloxane polymeric substrate, Fin‐M/CNT wires with a minimum width of 5 μm and a minimum pitch of 10 μm have been achieved. In addition, transparent Fin‐M/CNT grid lines with hexagonal patterns, with a sheet resistance of as low as 45 Ω sq −1, have been achieved at an optical transmittance of 88%.